PENGARUH PEMBERIAN BERBAGAI MACAM PUPUK DAUN TERHADAP PERTUMBUHAN TUNAS AKSILAR UBI JALAR (Ipomoea batatas L.) VARIETAS CILEMBU SECARA IN VITRO - Meriyanto .; Miranty Trinawaty; Nur Fitriani (Jurusan Agroekoteknologi Fakultas Pertanian Untirta, 2016)
Effect of foliar fertilizer on growth of axillary buds of sweet potato (Ipomoea batatas L.) Cilembu Variety as in vitro. This research was aimed to find inexpensive formulations planting medium for the multiplication of sweet potato as in vitro. Research was conducted at the Tissue Culture Laboratory of Faculty of Agriculture, University of Tridinanti Palembang from November 2015 until April 2016. The reseach used Randomized Completely Design (RCD) with 5 treatments and 5 replications, namely: H1 = MS (control), H2 = Hyponex 2 g, H3 = Growmore 2 g , H4 = Gandasil D 2g, H5= MS+Hyponex 2 g, H6 = MS+ Growmore 2g, H7=MS+Gandasil D 2g. Each treatment was repeated five (5) times. Parameter observed were: time formed buds, shoots, number of leaves, the time to form roots, number of roots, root length, and percentage of plantlets life. The result showed that the treatment of foliar fertilizer no significant effect than that of MS to spur the growth of axillary buds explants of sweet potato varieties Cilembu in vitro. In the tabulation of foliar fertilizer Growmore 2 g gave explant growth of axillary buds of sweet potato better.Keyword: Sweet potato, Foliar fertilizer.